Exploring highly porous Co2P nanowire arrays for electrochemical energy storage - Chen, Minghua; Zhou, Weiwei; Qi, Meili; Yin, Jinghua; Xia, Xinhui; Chen, Qingguo (Journal of power sources, 2017)
Controllable synthesis of mesoporous conductive metal phosphide nanowire arrays is critical for developing highly-active electrodes of alkaline batteries. Herein we develop a simple combined strategy for rational synthesis of mesoporous Co2P nanowire arrays by hydrothermal-phosphorization method. Free-standing mesoporous Co2P nanowires consisting of interconnected nanoparticles of 10–20 nm grow vertically to the substrate forming arrays. High electrical conductivity and large porosity are obtained in the arrays architecture. When characterized as the cathode of high-rate alkaline batteries, the designed Co2P nanowire arrays are proven with good electrochemical performance with a large capacity (133 mAh g−1 at 1 A g−1), stable cycling life with a capacity retention of almost 100% after 5000 cycles at 10 A g−1 owing to the mesoporous nanowire structure with short ion/electron transport path. Our synthetic approach can be useful for construction of other porous metal phosphide arrays for energy storage and conversion. Self-supported mesoporous Co2P nanowire arrays are prepared by a hydrothermal-phosphorization method and show good electrochemical performance with high capacity and stable cycling life. [Display omitted] •Construct self-supported mesoporous Co2P nanowire arrays.•Mesoporous Co2P nanowire arrays show high capacity and stable cycles.•Mesoporous nanowire arrays structure is favorable for fast ion/electron transfer.